Encouraging Outcomes of Alternate Donor Hematopoietic Stem Cell Transplant in Pediatric High-risk/Relapsed Leukemias: A Single Center Experience. Issue 8 (16th November 2021) - Sachdev, Mansi; Chakraborty, Sohini; Bansal, Minakshi; Bhargava, Rahul; Dua, Vikas
Abstract : Outcomes of high-risk and relapsed pediatric acute leukemias continue to be suboptimal. Allogeneic hematopoietic stem cell transplantation (HSCT) is the only curative modality. However, <30% of patients have matched sibling donors available. Hence, alternate donors (matched unrelated and haploidentical) are being used to improve outcomes. We retrospectively analyzed our data of all children with high-risk/relapsed acute leukemias who underwent alternate donor HSCT at our center from April 2015 to July 2020. A total of 15 patients were included—3 underwent matched unrelated and 12 underwent haploidentical HSCT. Before HSCT, all patients were in complete remission (CR): CR1-1, CR2-11, and CR3-3. All patients engrafted except one. Median time to neutrophil and platelet engraftment was 15 and 16 days, respectively. There were 3 transplant related mortalities. One patient was lost to follow-up. Remaining 11 patients remain in remission and are alive. The cumulative incidence of acute graft versus host disease was 57.1% and of chronic graft versus host disease was 21.4%. Overall survival was 80% and the event-free survival was 73.3%. The median follow-up of alive patients was 775 days (range: 333 to 2077 d). Our experience shows encouraging outcomes using alternate donor HSCT for these patients from developing world.